Process of Designing Model Eliciting Activities in Mathematics Teaching - İNCİKABI, Semahat; BİBER, Abdullah (Durmus Burak, 2021)
The aim of this study is to analyze prospective mathematics teachers’ process of designing model eliciting activities. Case study was preferred in this study. The study group of this research consists of 15 mathematics teacher candidates studying at Kastamonu University Faculty of Education Primary Mathematics Teaching Undergraduate Program during the academic year of 2019-2020. In this research, learning environments designed based on a holistic approach and based on "theoretical knowledge" were created. The research process took 10 weeks which are planned as mathematical modeling training process and MEA design process. Data of the study were collected through MEA design process worksheets. The data obtained from the data collection tool were subjected to content analysis. As a result of the research, it was determined that PMT groups included similar processes although there were some differences in the MEA design stages. The writing stages proceeded as determining the context of the MEA, deciding on variables and assumptions, writing the scenario and adding visual elements. In the control phase, the elements that the groups pay attention to include compliance with MEA principles, text control, visual editing, performing solution steps (model and data compatibility).
Keywords: 4. Education